Moral Sensitivity in Nurses Providing Care to Psychiatric Patients: A cross- sectional study - Duran, Songül; Kargın, Maral; Çelebi, Evrim (My University, 2018)
INTRODUCTION: In this study, it was aimed to determine themoral sensitivity of nurses who give care to psychiatricpatients.METHODS: This descriptive and cross-sectional study wasconducted between April and July 2017. The sample of thisresearch, a field that mental health care in the EasternAnatolia region in Turkey and 3 consisted of 105 nursesworking in hospitals and community mental health center.Data were collected via Personal Information Form and MoralSensitivity Questionnaire.RESULTS: The nurses participating in the study were found tohave high levels of moral sensitivity. It was determined thatorientation subscale scores of 30 year old and younger nursescomparing with nurses older than 30 and single nursescomparing with married ones were determined as higher.DISCUSSION AND CONCLUSION: Competence andresponsibility creation in psychiatric nursing education andpractice, and providing regular in-service training aftergraduation may be advised to create, maintain and improvemoral sensitivity of nurses.
Keywords: Hemşirelik; Psikoloji